(untitled) (Ibrahim Medical College Journal, 2009)
This case control study was conducted in selected centers of Dhaka City from March to July 2008 to determine the association of multidrug-resistant tuberculosis with the attributes related to treatment and socio-economic condition of tuberculosis patients. Sixty seven culture-proven multidrug-resistant tuberculosis cases and similar number of age and sex matched controls were selected purposively. Data were collected by face to face interview and documents’ review, using a pre tested structured questionnaire and a checklist. Multidrug-resistance was found to be associated with occupation (p=0.001) and residential status (p=0.001) of the tuberculosis patients. Tuberculosis patients who did not remain under directly observed treatment were 3 times more likely to develop multidrugresistant tuberculosis (OR 3.21, 95%CI=1.59-6.52). Multidrug-resistance was associated with inadequacy of treatment (OR 2.56, 95%CI=2.03-3.23). Failure of sputum conversion at the end of 2 months of treatment was detected to be the best predictor of multidrug-resistant tuberculosis (OR 11.82, 95% CI=4.61-30.33), followed by treatment with non Directly Observed Treatment Short course regimen and high labor intensive occupations like agriculture, production and transport. The risk factors of multidrug-resistant tuberculosis warrant much improvement in the effective implementation of control programs. Ibrahim Med. Coll. J. 2009; 3(1): 29-33 Key wards: Tuberculosis, MDR TB. doi: 10.3329/imcj.v3i1.2917